Pandangan Fukaha Kontemporer Tentang Hukum Bermuamalah dengan Bank Syariah - Atep Hendang Waluya (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2023)
The current performance of Islamic banking is quite encouraging, but for the market share of Islamic banking, which is currently still relatively small, even though the majority of Indonesia's population is Muslim. Knowledge or literacy has a significant influence on people's interest in muamalah with Islamic banks. This paper tries to describe contemporary jurists' views regarding the law dealing with Islamic banks. Contemporary jurists allow muamalah with Islamic banks because deposits in Islamic banks are built on the principle of mudaraba and there is no usury on it, this is as expressed by Wahbah al-ZuhaylÄ«, usÄmuddÄ«n 'AfÄnah, al-DubyÄn, Al-Qará¸ÄwÄ«, Islam Web, Ibn BÄz, DÄirat al-IftÄ and DSN MUI. According to DSN MUI wadiah or deposits in Islamic banks are yad dhamÄnah not yad amanÄh and according to Adiwarman Karim Islamic banks are allowed to give bonuses to customers if they are not required in advance, i.e. the gift is a voluntary gift given by the bank as its policy. According to contemporary fukaha, the law of saving in Islamic banks can be recommended in order to implement and enforce Islamic values